2007
DOI: 10.1111/j.1537-2995.2007.01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of general and traditional Chinese beliefs on the decision to donate blood among employer‐organized and volunteer donors in Beijing, China

Abstract: To recruit voluntary donors effectively in China and other countries with traditional cultures, efforts need to counteract traditional beliefs and perceptions of risk that discourage donation by emphasizing the benefits, safety mechanisms, physiology, and epidemiology of blood donation. In China, there is a rich opportunity to convert prior employer-organized donors into volunteer donors, and the institution of a confidential predonation screening system may help to facilitate truthful risk factor disclosure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 21 publications
1
60
0
1
Order By: Relevance
“…In traditional Chinese culture, blood is viewed as a nonrenewable vital energy source (Spector 2000). Donating blood is perceived as harmful to your health and can have a negative effect on one's life energy qi (Tison et al 2007). In the study conducted by Zaller et al (2005), 20 % of Chinese respondents stated they could not contribute blood because they felt it would weaken their body or because they had poor health (i.e., loss of qi).…”
Section: Discussionmentioning
confidence: 99%
“…In traditional Chinese culture, blood is viewed as a nonrenewable vital energy source (Spector 2000). Donating blood is perceived as harmful to your health and can have a negative effect on one's life energy qi (Tison et al 2007). In the study conducted by Zaller et al (2005), 20 % of Chinese respondents stated they could not contribute blood because they felt it would weaken their body or because they had poor health (i.e., loss of qi).…”
Section: Discussionmentioning
confidence: 99%
“…iii) Self-approval and self-respect: A study found 67.1% of whole blood donors were interested in donation because donating blood made them feel good about themselves [17]. Another study reported 23.0% of the surveyed platelet apheresis donors felt proud of themselves by blood donation [18].…”
Section: Donor Recruitmentmentioning
confidence: 99%
“…iv) Perceived health benefits: A study found 72.8% of donors felt that blood donation is beneficial to their own health; 30.2% thought donating blood could help get rid of fat [17]. Another survey found that 37.4% of voluntary donors believed that blood donation would produce positive health effects on themselves [8].…”
Section: Donor Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations